Becoming a Reading Teacher: Technical, Practical, and Critical Reflections on Service-learning in a Developmental Reading Course - Fontejon-Bonior, Gina A. (Silliman Journal, 2022)
This study investigated the extent to which reflections done by preservice teacher education students on a service-learning component of a Developmental Reading course demonstrated the technical, practical, and critical levels. Using axial coding, data from nineteen reading tutors’ journals and responses to an open-ended questionnaire were analysed to determine the level of reflection used and the merits, limitations, and promise of using reflective journals for the improvement of reading instruction and teaching in general. Findings suggest that although reflection is a crucial component of service-learning, its potential may only be fully exploited if students are provided specific or focused stimuli for reflection. Explicit instruction on the three levels of reflection may also be necessary to ensure that students go beyond mere description of their experiences.